Review Waktu Larut Mempengaruhi Kualitas Tablet Effervescent Sediaan Herbal - Sagala, Reynelda Juliani; Rachmawati, Putriana; Kambira, Pretty F.A (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
The effervescent tablet is an alternative dosage form to deliver the active pharmaceutical ingredients or natural products for therapeutic effects. Moreover, this dosage form is also used in the food industry for nutritional drinks. The tablet is preferred because of its practicality, improve water solubility, refreshing taste, and more easily absorbed than the conventional tablet. Tablet’s water dissolving time in the medium will affect the rate and amount of active ingredients. The disintegrating time of effervescent tablets is affected by the concentration of both acid and base elements, the tablet binder’s concentration (PVP), the interaction between citric acid and tartaric acid, and the concentration of the base element, the water content over the tablet, and the lubricant’s variation. The acid will affect the disintegration time however its imbalance will decrease the freshness. Therefore, an optimal balance of the base and acid element is required to make an effervescent tablet with a good disintegration time and an appropriate refreshing taste.